2020
DOI: 10.1016/j.ecresq.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years later: Locating and interviewing participants of the Chicago Longitudinal Study

Abstract: Retaining study participants over time is essential for longitudinal studies to prevent selection bias and to achieve their long-term goals. The present paper examines the extent to which participants can be retained in a 30-year longitudinal study when a multi-pronged approach is employed. The paper specifically describes the approach that was used to locate and interview participants of the Chicago Longitudinal Study (CLS), three decades after the study began. The CLS is a prospective cohort investigation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Originally implemented in public-school sites in Chicago in 1967, the CPC program offers a high-quality preschool through third-grade program emphasizing parental involvement to students and families in the city’s poorest neighborhoods. A long-running study called the Chicago Longitudinal Study (CLS) of a cohort of over 1500 students born in 1980 continues to follow these students into adulthood ( Ou et al, 2020 , Reynolds et al, 2018 ). The Child-Parent Center model regards parent involvement and engagement as one of its primary goals.…”
Section: Parent Involvement and The Child-parent Centersmentioning
confidence: 99%
“…Originally implemented in public-school sites in Chicago in 1967, the CPC program offers a high-quality preschool through third-grade program emphasizing parental involvement to students and families in the city’s poorest neighborhoods. A long-running study called the Chicago Longitudinal Study (CLS) of a cohort of over 1500 students born in 1980 continues to follow these students into adulthood ( Ou et al, 2020 , Reynolds et al, 2018 ). The Child-Parent Center model regards parent involvement and engagement as one of its primary goals.…”
Section: Parent Involvement and The Child-parent Centersmentioning
confidence: 99%
“…provide a detailed description of the approach that was used to locate and interview the participants in this study.Follow-up data at age 35 were available for a total of 1125 participants (retention rate = 73 %), 741 across the program group (75 % retention), and 384 across the comparison group (70 % retention). As reported inOu et al (2020), the retention rate in our study is higher than other large-sample (>200 participants) early childhood intervention studies such as the Infant Health and Development Program (65 % up to age 18), the Houston Parent-Child Development Center (63 % up to age 18), the Early Head Start Research and Evaluation Project (54 % up to age 10), and the Consortium for Longitudinal Study (55 % up to age 22).…”
mentioning
confidence: 58%
“…The survey was conducted between 2012 and 2017 and over 80 % of the respondents completed the interview via telephone. Ou et al (2020) provide a detailed description of the approach that was used to locate and interview the participants in this study.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we strive to offer flexible scheduling for interviews whenever we can (e.g., interview location, weekends, evenings). These strategies have been implemented in other long‐term longitudinal studies that also found them useful in keeping the retention rate high over the decades of the study course (Ou et al, 2020).…”
Section: Timeline Of Egds Assessments and Retention Rates Through Age 11mentioning
confidence: 99%